Pengaruh Pola Pelaksanaan Pemeliharaan Dental Unit Terhadap Ketahanan Dental Unit Di Rumah Sakit Gigi Dan Mulut Universitas Muhammadiyah Yogyakarta - Ageng Khresna S; Winny Setyo Nugroho (Program Studi Magister Manajemen Rumah Sakit, Jenjang Pasca Sarjana (S2), Pasca Sarjana Universitas Muhammadiyah Yogyakarta, 2018)
Background: Medical equipment is one of the factor that has been needed in Dental Hospital. Dental unit is one of medical equipment for the dentist to works with. Dental unit needs maintenance to keep it works properly. Dental hospital UMY has 76 dental units that have been functioned since 2008 and based on the report that conducted by technicians, there is no obstacle. Aim : This study is aimed to evaluate the implementation of dental unit maintenance conducted by dental student, dental nurse and dental technician toward dental unit durability in Dental Hospital UMY. Method : This study is an observational study with research design cross sectional. The research design of this study is cross sectional using mix method. Quantitative data using a questionnaire . Questionnaire will be used to determine the student knowledge about maintenance of dental units. Qualitative data using an indepth interview Indepth interview will be used to observe the implementation of dental unit maintenance conducted by dental nurses and dental technicians. Result : from the questionnaire data, 98% of dental coas have a good knowledge. From the interview data results the research found some damage in the supporting tool in dental unit that is handpiece, for the dental unit the condition is good, only small damage because to age of usage. besides that the other problems are the length of repair because lack of communication and has never existence of evaluation about maintenance has been running from 2008.